Anthocyanin supplementation inhibits secretion of pro-inflammatory cytokines in overweight and obese individuals. (January 2020) - Vugic, Lada; Colson, Natalie; Nikbakht, Elham; Gaiz, Almottesembellah; Holland, Olivia J.; Kundur, Avinash Reddy; Singh, Indu
Graphical abstract: Highlights: Anthocyanin's anti-inflammatory properties were investigated. ACN supplementation significantly decreases blood plasma levels of CCL2. ACN supplementation significantly decreases blood plasma levels of IL-6. ACN displays potential as a complementary anti-inflammatory therapeutic agent. Abstract: Chronic low-grade inflammation in obese and overweight individuals is associated with an increased risk of type II diabetes and cardiovascular disease. The current trial investigated the anti-inflammatory properties of anthocyanin (ACN) supplementation in lean, overweight and obese individuals. Fifteen lean, ten overweight and ten obese participants consumed ACN (320 mg/day) for 28 days along with their usual diet. ACN supplementation significantly decreased blood plasma levels of CCL2 in the lean, overweight and obese groups ( p  < 0.0001, p  < 0.0001 and p  < 0.01 respectively). Additionally, significantly decreased levels of IL-6 in the obese group ( p  < 0.05) were also observed post-ACN supplementation. In conclusion, these results demonstrate the anti-inflammatory potential of ACN and suggest the supplementation of ACN as a complementary therapeutic agent for reducing chronic inflammation in obese and overweight individuals.